2012
DOI: 10.4236/jct.2012.31010
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Toxicity of Metronomic Capecitabine in Advanced Hepatocellular Carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is a hypervascular tumor. Metronomic chemotherapy; the continuous administration of low-dose chemotherapy; has both cytotoxic and antiangiogenic effects with low toxicity profile. We evaluated the efficacy and toxicity of metronomic capecitabine (MC) in patients with advanced HCC. Patients and Methods: From May 2010, we enrolled pts with either metastatic or locally advanced diseases not candidate for ablative or locoregional treatment and have acceptable liver functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…Capecitabine, a prodrug of 5-fluorouracil (5-FU) metabolized to the active drug preferentially in liver and tumor tissue by thymidine phosphorylase (Walko and Lindley 2005), has been tested as first-and second-line treatment for HCC by some studies, using either the conventional or metronomic approach (Patt et al 2004;Lee et al 2009;Farrag 2012;He et al 2013;Abdel-Rahman et al 2013;Brandi et al 2013;Granito et al 2015;Murer et al 2016;Casadei Gardini et al 2017). The obtained results are sparse and rather conflicting, and only one of these studies compared capecitabine with best supportive care (BSC) in the setting of second-line therapy (Casadei Gardini et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capecitabine, a prodrug of 5-fluorouracil (5-FU) metabolized to the active drug preferentially in liver and tumor tissue by thymidine phosphorylase (Walko and Lindley 2005), has been tested as first-and second-line treatment for HCC by some studies, using either the conventional or metronomic approach (Patt et al 2004;Lee et al 2009;Farrag 2012;He et al 2013;Abdel-Rahman et al 2013;Brandi et al 2013;Granito et al 2015;Murer et al 2016;Casadei Gardini et al 2017). The obtained results are sparse and rather conflicting, and only one of these studies compared capecitabine with best supportive care (BSC) in the setting of second-line therapy (Casadei Gardini et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of metronomic capecitabine (MC) in patients with advanced HCC was first tested by Farrag, who described a modest anti-tumor efficacy and a low toxicity of this treatment (Farrag 2012). Three pioneering studies have shown that MC is active and well tolerated in both treatment-naïve and sorafenib-experienced patients (Brandi et al 2013;Granito et al 2015;Casadei Gardini et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, safety and efficacy of low dose of doxorubicin and 5 FU along with supportive treatment were evaluated compared to best standard of supportive care alone in patients with advanced HCC, the overall response was 16.7 % (PR) with disease control of 70% (16.7% PR, 53,3% SD and 0% CR) in treatment arm compared with 0 % OARin control arm, this results differ from the results achieved by previous studies e.g. Yeo et al [11] who studied doxorubicin versus (PIAF) combination chemotherapy in patients with HCC carcinoma, where the OAR was 20.9% in the treatment arm, and Qin et al [22] who studied the efficacy and survival benefits of FOFOX4 compared to doxorubicin in patients had advanced HCC, where the RR was 8.15% in FOLFOX4 arm, this difference may be due to small number of the patients in our study, all patients were Child class A and most patients had received primary treatment for localized disease before enrollment in this study, but in another study conducted in Egypt by Farrag A [18] evaluating the role of metronomic dose of capecitabine in patients with advanced HCC, the RR was 16% and disease control was 69%, nearly the same results obtained in our study, however, our protocol less expensive and more compliant with the patients. Generally, regarding RR, the results obtained in this study are comparable to or slightly better than the results obtained in other studies evaluating old and newer chemotherapeutic agents in the treatment of advanced HCC.…”
Section: Discussionmentioning
confidence: 65%
“…In addition to smaller absolute survival benefits in patients with macrovascular invasion and/or extrahepatic spread, drug availability and its costs are the major challenges for its use especially, in developing countries as Egypt. So, the role of sorafenib in advanced HCC should be conformed, and additional trials of other possible systemic chemotherapeutic agents are also needed, especially after the promising results of some other chemotherapeutic regimens [18][19][20] . The role of systemic chemotherapy in the treatment of advanced HCC was evaluated and reviewed in many studies [17,21] .…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Brandi et al [16] they used MC at a dose of 500 mg twice daily till disease progression or toxicity and indicated that MC is well tolerated by patients with advanced HCC and appears to have activity both in treatment-naive patients and in those previously treated with sorafenib. Also, Farrag et al [25] studied MC in patients with advanced HCC at a dose of 1,000 mg/m 2 /day without interruption and showed modest antitumor activity and low toxicity profile. Based on these data, patients in our study received MC at a dose of 500 mg twice daily continuously without interruption.…”
Section: Discussionmentioning
confidence: 99%